Evaluation of the reverse mortgage option in Korea: A long straddle perspective - Kyung Jin Choi; Byungkwon Lim; Jaehwan Park (International Journal of Financial Studies, 2020)
This study explored the option value embedded in a reverse mortgage in Korea through an empirical analysis, using the Black-Scholes option-pricing model. The value of a reverse mortgage is affected by the variation in house prices. However, older homeowners using reverse mortgages are able to choose this option due to the unique characteristics of reverse mortgages, such as non-recourse clauses or being able to redeem the loan. This paper found the following results. First, the call option value is 5.8% of the house price at the age of 60, under the assumption of a KRW three hundred million house value, while the put option value is only 2.0%. Contrary to what it is at sixty years of age, only the call option value will remain when the homeowner reaches the age of 80. Second, this article analyzed the sensitivity of the key variables of real-option analytical models, such as the change of the exercise price, the change of the risk-free rate, volatility, and maturity, on the option value of a reverse mortgage. The sensitivity results of the key variables supported economic rationales for the option pricing model.
Keywords: C58; G17; G21; H55; 330; reverse mortgage; straddle; European option; Black-Scholes option-pricing model